ECOLOGICAL IMAGINATION IN CONTEMPORARY JAPANESE AND HINDI LITERATURE - Kumar, Pankaj (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The concept of ecological imagination has undergone a significant transformation in contemporary Japanese and Hindi literature, reflecting a paradigmatic shift in the portrayal of nature from a passive, aestheticized entity to an interconnected, dynamic force. This paper explores the evolution of literary perspectives in Japanese and Hindi literature on nature, moving beyond anthropocentric representations toward an “Ecological Turn” that emphasizes the sublime, autonomous, and interdependent aspects of the natural world. Drawing from cultural and philosophical frameworks such as Shinto animism in Japan and Indian cosmological traditions, this study examines how these literary traditions engage with deep ecological themes to critique environmental degradation and advocate for ecological preservation. Through a comparative analysis of contemporary Japanese literature such as Ishimure Michiko’s Lake of Heaven and Hindi Literature such as S. R. Harnot’s Ek Nadī Taḍaptī Hai (A River’s Agony), this paper highlights the ways in which both works employ narrative strategies to foreground environmental concerns. Michiko’s novel reflects on the cultural and ecological devastation wrought by large dam projects, portraying the loss of traditional ways of life and advocating for a renewed sensitivity to nature. Similarly, Harnot’s work underscores the destructive consequences of industrialization on rivers, revealing the existential distress inflicted upon both human communities and natural ecosystems. By shifting from an anthropocentric to an eco-centric worldview, both authors emphasize the intrinsic relationship between nature and culture, calling for a deeper engagement with ecological consciousness.